Notes on the genus Afropachyiulus Schubart, 1960 (Diplopoda: Julida: Julidae) with a description of a new species from Algeria and a redescription of A. comatus (Attems, 1899) - Akkari, Nesrine; Enghoff, Henrik (Zootaxa, 2008)
The North African genus Afropachyiulus Schubart, 1960 is a poorly defined genus of the tribe Pachyiulini, the taxonomy of which is still obscure. In this paper we retrace the history of the genus Afropachyiulus, we describe A. mauriesi n. sp., from Algeria, and we redescribe the very similar A. comatus (Attems, 1899) from Tunisia based on type and new material.